An Analysis of Logical Transitions in Sam Chui’s Review of Emirates Airline - Euro Hokiarto Tanjung; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2025)
This research investigates the use of logical transitions in Sam Chui’s reviews of Emirates Airline, which consist of one YouTube video and one blog article. By applying Robert A. Harris’s (2018) framework—Metabasis, Procatalepsis, and Hypophora—the study adopts a qualitative approach, supported by quantitative data to address the third research question concerning frequency and distribution. The findings reveal that, although all three types of transitions appear in both platforms, their usage patterns differ. In the video, Metabasis is used most frequently (42.10%), followed by Procatalepsis (31.57%) and Hypophora (26.31%). Meanwhile, in the blog article, Metabasis is more dominant too (69.56%), with Procatalepsis and Hypophora less often at 26.08% and 4.34%, respectively. These variations seem to stem from the inherent differences between spoken and written communication. While blog readers rely on explicit textual signals to navigate content at their own pace, video viewers benefit from visual and auditory cues that ease transitions without requiring overt markers. As such, written discourse tends to emphasize structural cohesion through devices like Metabasis. Although limited in scope, this study offers insights into how rhetorical strategies vary across media formats, contributing to digital discourse and multi-discourse communication studies.